Experimental investigation on the characteristics of the dynamic rail pad force and its stress distribution in the time and frequency domain. (February 2020) - Zhang, Xu; Zhao, Chunfa; Ren, Xiaobo; Feng, Yang; Shi, Can; Zhai, Wanming
The rail pad force and its stress distribution have critical influences on the performance and fatigue life of the rail, fasteners, and sleepers. The characteristics of the rail pad force and its stress distribution in the time and frequency domain obtained from field tests carried out using matrix-based tactile surface sensor are presented in this paper. The field testing involved rail pads under various axle-loads of running trains at different speeds. The influences that the train axle-load, the operational speed, and the rail pad stiffness have on the rail pad force and its stress distribution are analyzed. The test results indicate that the rail pad stiffness has a remarkable influence on the amplitude of the rail pad force but has little influence on its dominant frequencies. The first dominant frequency of the rail pad force is quite close to the passing frequency of the vehicle length. The stress distribution on the rail pad has a parabolic shape along the longitudinal and the lateral directions with the large stress appearing near the center of the rail pad, and is remarkably affected by the service condition of the rail pad. The maximum stress is about 2.5 to 3 times of the average stress, which is significantly greater than the nominal stress resulting from the assumption of uniform stress distribution.